2004
DOI: 10.2460/ajvr.2004.65.1701
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pituitary gland anatomy and histopathologic findings in clinically normal horses and horses and ponies with pituitary pars intermedia adenoma

Abstract: Objective—To determine size and weight of the pituitary gland and associations between pituitary gland size and weight and sex and age in horses without clinical signs associated with pituitary pars intermedia adenoma (PPIA) and horses and ponies with PPIA. Animals—Pituitary glands from 100 horses without clinical signs of PPIA and 19 horses and 17 ponies with PPIA. Procedures—Pituitary glands were weighed, measured, and examined histologically by use of H&E stain. Masson trichrome and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Horses with PPID often also have increased plasma α-MSH levels, which have also been correlated with an increased BCS [14]. Unfortunately, since previous research has shown that histologic lesions in the pars intermedia do not always correlate with clinical signs [25], and since horses in the current study did not undergo diagnostic testing for PPID, the health implications of concurrent IR and pituitary lesions require further study. The results of this study, do, however, confirm previous reports that increasing pituitary scores are correlated with increasing age [18] [20].…”
Section: Discussionmentioning
confidence: 77%
“…Horses with PPID often also have increased plasma α-MSH levels, which have also been correlated with an increased BCS [14]. Unfortunately, since previous research has shown that histologic lesions in the pars intermedia do not always correlate with clinical signs [25], and since horses in the current study did not undergo diagnostic testing for PPID, the health implications of concurrent IR and pituitary lesions require further study. The results of this study, do, however, confirm previous reports that increasing pituitary scores are correlated with increasing age [18] [20].…”
Section: Discussionmentioning
confidence: 77%
“…The gelding remained bright, with a good appetite, and no further weight loss occurred until the horse was subjected to euthanasia 1.5 months after admission as dictated by the protocol of the research study. Post mortem examination confirmed PPID (pituitary gland weight 5.8 g and PPID grade 5/5 ; pituitary weight/body weight, 15.7 × 10 −6 g, range in normal animals, 4.2–8.5 × 10 –6 g) , but no abnormalities of the liver or other tissues were reported.…”
Section: Casementioning
confidence: 89%
“…), with those suffering from pituitary pars‐intermedia dysfunction (PPID) measuring on average 2.6 ± 0.3 cm rostrocaudal length, 2.4 ± 0.26 cm laterolateral width, and 1.92 ± 0.43 cm dorsoventral height (Kolk et al . ). Enlarged pituitary glands can also be found in horses with no neurological signs and without PPID.…”
Section: Discussionmentioning
confidence: 97%
“…; Kolk et al . ; Crijns et al . ), with those suffering from pituitary pars‐intermedia dysfunction (PPID) measuring on average 2.6 ± 0.3 cm rostrocaudal length, 2.4 ± 0.26 cm laterolateral width, and 1.92 ± 0.43 cm dorsoventral height (Kolk et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation